Pengaruh Pemberian Minyak Biji Rami Per Oral terhadap Peningkatan Jumlah Osteoblas pada Tikus Putih Jantan Galur Sprague Dawley dengan Periodontitis - Ketut Virtika Ayu (Maranatha Christian University, 2022)
The orthodontic treatments of dentistry is to correct malocclusions. However, these treatments are difficult due to periodontal disorders involving alveolar bone resorption. Periodontitis is a chronic inflammatory disease leading to tooth loss. Flaxseed oil contains high omega-3 that can reduce inflammatory activity thereby reducing bone resorption. This study was conducted to prove the flaxseed oil enhance the osteoblasts number in periodontitis rats. This study was a purely experimental research with Randomized Post Test Only Control Group Design. Research subjects consisted of 8-12 week 32 white male rats of Sprague Dawley strain were divided into 2 groups; a control group were given placebo (glycerin) orally for 21 days, whereas the treatment group were given flaxseed oil 700 mg/200grBW orally for 21 days. On the 30th day, mice were euthanized for mandibula alveolar bone tissue sampling and histological preparations were made by HE (Harris Hematoxylin-Eosin) staining. The data were analyzed using SPSS program processed using Shapiro-Wilk for normality test and then continued using the independent t-test. The results showed that the mean of osteoblasts number at the treatment group by oral administration of flaxseed oil (64.62 ± 4.288 cells per 5 field of view) was significantly higher than the control group (36.56 ± 3.483 cells per 5 field of view). Test results based on comparison between the control group and the group treated with flaxseed oil with independent t-test showed that significant differences in the osteoblasts number and bone density of white male Sprague Dawley rats (p<0.05). This study concluded that there’s effect of oral administration of flaxseed oil enhance the osteoblasts number in white male rats of Sprague Dawley strain with periodontitis. Keywords: flaxseed oil, periodontitis, osteoblasts